Prawda kobieca obiektywna a całkowita w utworach Walentina Rasputina - Kompaniejec, Walerij (Studia Rossica Posnaniensia, 2012)
The artistic characterology of Valentin Rasputin is considered from the angle of the gnosiological categories of truth. The characters are interpreted in the gender aspect. The author concentrates on stories by V. Rasputin, mainly, on the work Zhivi y pomni (Live and Remember).